Critical Study of the Recognition between C-Reactive Protein and Surface-Immobilized Phosphorylcholine by Quartz Crystal Microbalance with Dissipation - Wu, Jhih-Guang (Langmuir : the ACS journal of surfaces and colloids, 2018)
C-reactive protein (CRP), a biomarker for cardiovascular disease, has been reported to have a strong affinity to zwitterionic phosphorylcholine (PC) groups in the presence of calcium ions. In addition, PC-immobilized surfaces have been used as a nonfouling coating to prevent nonspecific protein binding. By appropriately using the features of PC-immobilized surfaces, including specific recognition to CRP and nonfouling surface, it is reasonable to create an antibody-free biosensor for the specific capture of CRP. In this study, PC-functionalized 3,4-ethylenedioxythiophene (EDOT) monomers were used to prepare PC-immobilized surfaces. The density of PC groups on the surface can be fine-tuned by changing the composition of the monomer solutions for the electropolymerization. The density of PC group was confirmed by X-ray photoelectron spectroscopy (XPS). The specific interaction of CRP with PC groups was monitored by using a quartz crystal microbalance with dissipation (QCM-D). The amount of protein binding could be estimated by the reduction in frequency readout. Through the QCM-D measurement, we revealed the nonfouling property and the specific CRP capture from our PC-immobilized surfaces. Notably, the dissipation energy also dropped during the binding process between CRP and PC, indicating the release of water molecules from the PC groups during CRP adsorption. We anticipate that surface-bound water molecules are mainly released from areas near the immobilized PC groups. Based on Hofmeister series, we further examined the influence of ions by introducing four different anions including both kosmotrope (order maker) and chaotrope (disorder maker) into the buffer for the CRP binding test. The results showed that the concentration and the type of anions play an important role in CRP binding. The present fundamental study reveals deep insights into the recognition between CRP and surface-immobilized PC groups, which can facilitate the development of CRP sensing platforms